Examination of the Effects of Video Prompting Across Different Types of Tasks. (November 2018) - Cannella-Malone, Helen I.; Jimenez, Eliseo D.; Schaefer, John M.; Miller, Megan; Byrum, Hollie
Video prompting has a strong evidence base as an effective strategy to teach students with severe disabilities a variety of skills including daily living skills. This study examined whether differences in daily living tasks (i.e., multistep, multicomponent, and sequential tasks) would impact skill acquisition using video prompting by three participants with severe to profound disabilities. Results indicated that although video prompting was effective broadly, aspects of task type taught may affect the pace of an individual's acquisition. Implications for future research and practice are discussed.